Forest composition, structure, and regeneration in a dry forest of the Nicaraguan Pacific coast - Sabogal, C.; Valerio, L. (1998)
This paper presents the results of nearly five years of research in one of the least disturbed dry forests in Nicaragua, the country with the largest proportion of dry forest areas in Central America. Floristic, structural and dynamic aspects of dry deciduous and gallery forest stands are presented. The study has international implications because knowledge of tropical dry forest ecology is scarce at the same time that local demands on such forests around the world are intense.